Passively mode-locked thulium doped fiber laser based on SnSe nanoparticles as a saturable absorber. (June 2021) - Ma, Xiaohui; Zhang, Zhengxiong; Jiang, Wenhui; Tong, Liang; Liu, Shaoqing; Dai, Wenwen; Chen, Wu; Zhou, Yong; Zhang, Wei; Qiu, Jihong; Liao, Meisong; Gao, Weiqing
Highlights: Mode-locking operation at 1963 nm in a Tm-doped fiber laser. SnSe nanoparticles deposited on a D-shaped fiber as a saturable absorber. Harmonic mode-locking from the second order to the eighth order. Repetition rate of 24.59 MHz and pulse width of 1.2 ps. Abstract: In this paper, tin selenide (SnSe) nanoparticles (NPs) are employed as a saturable absorber (SA) in a passively mode-locked thulium (Tm)-doped fiber laser for the first time. The mode-locked pulse has a central wavelength of 1963 nm and a 3-dB bandwidth of 4.3 nm. The repetition rate is 24.59 MHz and the full width at half maximum (FWHM) of the pulse is 1.2 ps. Harmonics from the second order to the eighth order are observed. Our results prove that the SnSe have excellent nonlinear saturable absorption properties and could have wide potential applications on ultrafast photonics in mid-infrared waveband.